2007
DOI: 10.1093/glycob/cwm059
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sorting of galectin-8 based on carbohydrate fine specificity

Abstract: Galectin-8 has two carbohydrate recognition domains (CRDs), both of which bind beta-galactosides, but have different fine specificity for larger saccharides. Previously we found that both CRDs were needed for efficient cell surface binding and signaling by soluble galectin-8, but unexpectedly binding of the N-CRD to its best ligands, alpha2-3-sialylated galactosides, was not needed. In search for another role for this fine specificity, we now compared endocytosis of galectin-8 in Chinese hamster ovary (CHO) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 33 publications
5
34
0
Order By: Relevance
“…Consistent with this, a recent study on the N-terminal domain of Gal-9 (Gal-9N) demonstrated that it is also a dimer, as evidenced by studies of the crystal structure and solution-based experiments (53). Although we found that only the C-terminal domain of Gal-8 binds the functional signaling receptors on HL60 cells, the unique binding properties of each separate domain corroborates previously studies (29,35,54) and suggests that different cells may possess unique sensitivity to the potential signaling effects of each individual domain (28,55). Furthermore, because the N-terminal domain of Gal-8 intrinsically dimerizes, cleavage of the linker region between Gal-8N and Gal-8C may allow regulatory circuits to dissect potential signaling pathways initiated by each separate domain.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this, a recent study on the N-terminal domain of Gal-9 (Gal-9N) demonstrated that it is also a dimer, as evidenced by studies of the crystal structure and solution-based experiments (53). Although we found that only the C-terminal domain of Gal-8 binds the functional signaling receptors on HL60 cells, the unique binding properties of each separate domain corroborates previously studies (29,35,54) and suggests that different cells may possess unique sensitivity to the potential signaling effects of each individual domain (28,55). Furthermore, because the N-terminal domain of Gal-8 intrinsically dimerizes, cleavage of the linker region between Gal-8N and Gal-8C may allow regulatory circuits to dissect potential signaling pathways initiated by each separate domain.…”
Section: Discussionsupporting
confidence: 91%
“…Galectin-3 was rapidly taken up by the SKBR3 cells, as expected from other cell types (33,34) (Fig. 4B), and was after 24 h found in both large and small vesicular structures in the cytosol (Fig.…”
Section: Figure 2 Quantitation Of Total Proteins and Galectin-3-bounsupporting
confidence: 68%
“…Notably, the N-terminal CRD of Gal-8 can bind to type 1 LacNAc, but the C-terminal CRD of Gal-8 has a higher binding affinity for poly-LacNAc structures (40). The differential biological activities of the N-versus C-terminal CRD of Gal-8 have been shown (41), including in killing E. coli strains (42), in activating platelets (43), and in modulating neutrophil function (44); however, which CRD of Gal-8 is responsible for its positive role in plasma cell formation remains to be determined. In the current study, sulfomodified Gals or GlcNAc on type 1 or type 2 LacNAcs were used as competitors to elucidate the binding ligands for Gal-1 and Gal-8 on mature B cell surfaces.…”
Section: Discussionmentioning
confidence: 99%